Collection de passions = Passion de collections : La Fondation des Treilles. - Bourjade, Anne; Giraudy, Danièle; Gruner Schlumberger, Anne; Stella, Dominique; de Saint Pulgent, Maryvonne (Milano : Galleria Gruppo Credito Valtellinese Milano, 2007)
Arp, Hans (Jean) ; Brauner, Victor ; Dubuffet, Jean ; Ernst, Max ; Fautrier, Jean ; Fernandez, Luis ; Giacometti, Alberto ; Hadengue, Sébastien ; Klee, Paul ; Lalanne, François-Xavier ; Laurens, Henri ; Leger, Fernand ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Picasso, Pablo ; Réquichot, Bernard ; Séférian, Chouchanik ; Sima, Joseph ; Sklavos, Yerassimos ; de Soria, Claude ; Takis ; Vieillard, Roger
Collection de passions = Passion de collections : La Fondation des Treilles, Galleria Gruppo Credito Valtellinese Milano, 2007-03-02. 2007-05-30
boek